Prácticas maternas de alimentación en niños de 6 a 24 meses atendidos en establecimientos de salud de Lima e Iquitos - Rojas-Guerrero, Nady (2019)
Introduction. Poor complementary feeding practices have a negative effect on the growth and development of children in early childhood. Peru is a country with a wide cultural diversity and varied idiosyncrasies about the nutrition of children. In that context there are not publications about that topic. It has not been evaluated if there are differences between complementary feeding practices according to the region of residence. Objective. Determine the maternal feeding practices of children from 6 to 24 months attended in a health facilities in Lima and Iquitos. Methods. The unit of analysis was the mother-child couple. A total of 151 couples were considered in Lima and 168 in Iquitos. To establish the relation between complementary feeding practices and the city of origin, Chi square test with a level of significance of 0,05 was used. Results. 174 (54,55%) were female, 191 (59,87%) of the children were between 12 and 24 months old. The mothers had a median age of 25 years. There was a significant difference between the compliance rates of exclusive breastfeeding before 6 months between Lima and Iquitos (p = 0,007), compliance with the minimum acceptable diet (p = 0,000) and consumption of multimicronutrients (p = 0,000). Conclusions. The differences between complementary feeding practices for Lima and Iquitos are a higher frequency of non-compliance with exclusive breastfeeding and consumption of multimicronutrients for Lima, and a higher frequency of noncompliance with a minimum acceptable diet for Iquitos.